Landmark detection for vision based of autonomous guided vehicle - Nurul Atiqah Syazwani, Kamarudin (2012)
The creation of Autonomous Guided Vehicle (AGV) gives many advantages in our lives. This thesis is focused on navigation control system for an Autonomous Guided Vehicle (AGV) by detecting and recognizing artificial landmark with using USB webcam. USB webcam act as sensor that provides the appropriate information for the AGV navigation and landmark detection. This project involved single vision system. The aim of this project is to develop an algorithm for vision based AGV. Several image processing pipelines involved in this project. The algorithm is developed not only to detect and recognize but also to distinguish landmark from non-landmark. Non-landmark might possibly have the same features or characteristic with landmarks. The landmarks must be detected and recognized by vision sensor accurately in a real-time. The landmarks are in the form of shape that consists of command for the movement, direction and position of AGV. The key study in this project is the algorithm design.